Gaming Disorder in Individuals Experiencing Stress: Cognitive Attentional Syndrome and Metacognitions as Mediators - Çakıcı, Kardelen; Denizci Nazlıgül, Merve (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: The present study examined the mediator roles of cognitive attentional syndrome and metacognitions about online gaming on the relationship between perceived stress and gaming disorder. A total of 1459 participants (Mage = 23.97; SD = 5.00, from 18 to 54) were recruited through social media and asked to fill out the Perceived Stress Scale, Cognitive Attentional Syndrome 1 Scale, Metacognitions about Online Gaming Scale, and Internet Gaming Disorder Scale—Short Form. Path analysis was carried out via AMOS 24 to test the proposed model. The findings revealed that there was a significant indirect effect of perceived stress on gaming disorder through negative metacognitions about online gaming, through cognitive attentional syndrome and positive metacognitions about online gaming, and through cognitive attentional syndrome and negative metacognitions about online gaming. In addition, results were discussed while taking into account the underlying mechanisms of metacognitive processes for addictive behaviors and limitations, suggestions for future studies, and clinical implications were considered. In conclusion, this study contributed to the literature with its findings that fit the theoretical model of The Self-Regulatory Executive Function concerning gaming disorder.
Keywords: Cognitive attentional syndrome; gaming disorder; metacognitions; perceived stress